Desperately seeking depth: global and local narratives of the South African general elections on television news, 1994 - 2014 - Jones, Bernadine (Centre for Film and Media Studies, 2018)
Eric Louw, Jesper Stömbäck, and W. Lance Bennett call the trend in late-20th century political journalism "mediatisation", where the televisualisation of Western elections favours episodic, dramatic, fragmented, and event-driven reporting. This "hype-ocracy" results in narrow and shallow frames that entertain rather than enlighten. This thesis, titled "Desperately Seeking Depth", examines this trend in both international and local news about South African elections. While scholarship of Western elections on TV news is blossoming, analyses of news coverage of South African elections is sparse. There is particularly little analysis of the visual dimensions of TV news coverage, which remains a methodological challenge for media and communication scholars. This thesis draws together a comprehensive analysis of South Africa's general elections on international and local television news over two decades. It develops an innovative, multimodal analysis method dedicated to television news and adds meaningful data to the overall study of South African media and politics, and international communication. It combines analysis of previous studies of each election with the original analysis of over 150 news broadcasts to uncover the news narratives about the South African general elections between 1994 and 2014. This thesis demonstrates the difference between global and local journalism about South African elections. Restricted by mediatised news values that favour episodic reporting, Western journalists present entangled, contradictory narratives over the years. The fixation on 1994's violent-turned-miracle election narrative ignored the complexities of the new democracy, while an increasingly detached approach in covering the 2009 and 2014 ANC victories left journalists perplexed and unable to explore deeper narratives. Meanwhile, South African channels become progressively more hesitant to investigate controversial topics or criticise the ruling party. Avoidance of important issues such as the 1994 election violence, the AIDS crisis in 2004, and Zuma's Nkandla fiasco in 2014 results in narrow reporting that limits the substantive information available during the election periods. All channels to some extent seek narratives that attempt to explain and explore South Africa's complex democracy, but these narratives are often contradictory. The decline in journalists' engagement with political leaders and citizens means that the full picture of the elections is reduced to a few easily digestible frames that confirm neoliberal news values. This thesis offers a new model for the analysis of TV news coverage of elections that can provide the basis for future studies. "Desperately Seeking Depth" ultimately uncovers a picture of news industry that, both locally and globally, works as an echo chamber of sound bites that focused on elite voices.